Digital Transformation at Bandung Wholesale Center: The Impact of Information Technology on Sales Performance and Experience - Syaifuddin, Syaifuddin; Puad, Noor Aimi Mohamad (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2025)
This study examines the impact of digital transformation on sales performance and customer experience in wholesale centers in Bandung, specifically focusing on the adoption of digital inventory management systems, electronic payment platforms, and mobile applications, including the use of TikTok and Instagram for digital marketing. The study aims to analyze how these technologies improve operational efficiency, transaction speed, and customer satisfaction in the wholesale sector. A mixed-method approach was used, combining qualitative and quantitative data. Qualitative data was obtained through in-depth interviews with 10 wholesale center owners and managers, while quantitative data was collected through a survey distributed to 200 customers. Purposive sampling was used to select wholesale centers that had adopted digital technology. The findings show significant improvements in operational efficiency, with inventory checking time reduced by 66.67% (from 12 hours to 4 hours), stock errors reduced by 66.67% (from 15% to 5%), and order fulfillment speed increased by 50% (from 2 days to 1 day). The use of TikTok and Instagram in digital marketing has expanded market reach, increased customer engagement, and raised brand awareness. In addition, electronic payment systems and mobile applications have accelerated transactions, reduced queues, and increased sales volumes. Customers reported higher satisfaction, with ease of transaction increasing by 40.63% and overall satisfaction increasing by 31.43%. This study supports existing literature on the benefits of digitalization in retail and highlights challenges such as investment costs and staff training. These findings offer important insights for the wholesale sector to embrace digital transformation to increase competitiveness in an increasingly digital marketplace.